Thermophysical properties database of materials for light water reactors and heavy water reactors : final report of a coordinated research project, 1999-2005. (IAEA-TECDOC, 2006)
The thermophysical properties database for materials of light water reactors and heavy water reactors described in this technical document was established within the framework of an IAEA Coordinated Research Project. he database is intended to serve as a useful source of information on thermophysical properties data for water cooled reactor analyses. In particular, it aims at achieving improvements in safety and economics of future plants by helping to remove the need for large design margins to account for limitations of data and methods. It has been developed into an internationally available Internet database (THERPRO) at Hanyang University (Republic of Korea), and now provides various materials properties data and an interactively accessible information resource and communications medium for researchers and engineers.--Publisher's description.